Inter‐individual differences in weight change following exercise interventions: a systematic review and meta‐analysis of randomized controlled trials. (27th April 2018) - Williamson, P. J.; Atkinson, G.; Batterham, A. M.
Summary: Previous reports of substantial inter‐individual differences in weight change following an exercise intervention are often based solely on the observed responses in the intervention group. Therefore, we aimed to quantify the magnitude of inter‐individual differences in exercise‐mediated weight change. We synthesized randomized controlled trials (RCTs) of structured, supervised exercise interventions. Fourteen electronic databases were searched for relevant studies published up to March 2017. Search terms focused on structured training, RCTs and body weight. We then sifted these results for those RCTs ( n  = 12, 1500 participants) that included relevant comparator group data. Standard deviations (SDs) of weight change were extracted, thereby allowing the SD for true inter‐individual differences in weight loss to be calculated for each study. Using a random effects meta‐analysis, the pooled SD (95% CI) for true individual responses was 0.8 (−0.9 to 1.4) kg. The 95% prediction interval (based on 2SDs) for true inter‐individual responses was −2.8 to 3.6 kg. The probability (% chance) that the true individual response variability would be clinically meaningful (>2.5 kg) in a future study in similar settings was 23% ('unlikely'). Therefore, we conclude that evidence is limited for the notion that there are clinically important individual differences in exercise‐mediated weight change.